KNOWLEDGE AND PERCEPTION OF THE PUBLIC AND PUMP ATTENDANTS ON THE SITING OF FUEL STATIONS IN THE TAMALE METROPOLIS - Akuffo, A.; Cobbina, S. J.; Aboka, E. Y. (UDS International Journal of Development, 2019)
Tamale is a fast growing city which is currently witnessing an increase in the number of fuel stations that are sited close to public places especially stores, hospitals, and other commercial areas. The main aim of the study was to examine the knowledge and perceptions of pump attendants and the general public on the siting of fuel stations in the Tamale Metropolis. Stratified random sampling was used to select 25 fuel pump attendants, and 100 public respondents. Data was collected through field observation and questionnaire was used to elicit information on the knowledge level and perception of respondents. A Chi-square test was used for hypotheses testing (H1). The study found that many of the pump attendants were very knowledgeable on safety and health, and organisational requirement at the fuel stations. Knowledge of pump attendants on safety and health showed little relationship with knowledge on organisational requirements (p = 0.024). Most public respondents stated that fuel stations are sited inappropriately within the Metropolis. The study also revealed that profit was the major factor that influenced fuel station siting. Also, respondents attested that air pollution and respiratory problems were the major environmental and health effects associated with fuel stations. Based on the findings of the study, there is the need for intense public education on the menace associated with the siting and operation of fuel stations in order to prevent and manage likely risks and disasters from occurring in the same or greater magnitude as the twin disaster on 3rd June 2015. Keywords: Knowledge, Perception, Pump Attendants, Fuel station, Tamale